DEVELOPMENT OF MATHEMATICS MODULE ALGEBRA MATERIAL FOR CLASS VII OF JUNIOR HIGH SCHOOL - Awang Qomari; Sunaryo Sunaryo (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Teachers are required to innovate in the learning process, which is a determinant of students' ability to understand the classroom materials. One of the innovations is to make learning media, but in reality, the availability of available media is still limited. The research aims to design, create, and describe whether or not the Development of E-Learning Based Mathematics Learning Media using Moodle for Student Class VII of Junior High School (SMP) in Subject Matter of Algebra. This research is focused on the development of mathematics learning media, which is packaged in internet form. This development research using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). His research subjects are material experts, media experts, and student's responses of SMP 1 Muhammadiyah Prambanan and SMP Muhammadiyah 17 Prambanan Klaten. Data analysis techniques use qualitative analysis and quantitative values. Data collection techniques used questionnaires. The research instruments used material expert questionnaires and instructional media experts as well as student response questionnaires. This research has succeeded in developing math learning media that have Good Quality (GQ). With the average score of an expert material assessment, 85,667 have Excellent Quality (EQ), and the average score of media expert assessment results was 38,333 with GQ. While the student response score 65,2 has EQ with scores on small class trials and 62,122 large class trials with GQ. Based on these assessments, this math learning media is worthed to be used as a learning resource.